THE ROLE OF THE PUBLIC PROSECUTOR AS AN IMPLEMENTER COURT DECISION IN A CASE THAT HAS BEEN PERMANENT LEGAL FORCE - Nurita, Cut; Lubis, Muhammad Ridwan; Lubis, Muhammad Ansori (Jurnal Ilmiah METADATA, 2025)
The implementation of a judge's decision that has permanent legal force is the most important part of the judicial process because this is where true justice is upheld . The role of the public prosecutor as the implementer of court decisions in criminal cases that have permanent legal force is to be able to carry out execution based on excerpts from court decisions. A copy of the decision or excerpt of the decision (criminal) that has been sent to the parties (defendant and prosecutor), then the excerpt of the criminal decision can be used as a basis for execution, because it contains the verdict or dictum of the decision, but the legal considerations are no longer included. The mechanism for implementing court decisions in criminal cases that have permanent legal force is that the clerk must send a copy of the decision to the prosecutor's office to be implemented by the public prosecutor. The obstacles faced by the public prosecutor in implementing court decisions in cases that have permanent legal force are the messengers who have permanent legal force but the copy of the decision has not been submitted to the prosecutor's office, the public prosecutor's efforts in facing obstacles in implementing court decisions that have permanent legal force are to coordinate with the relevant courts to immediately send a copy of the decision to the prosecutor's office.